Comparison of the complete mitochondrial genome of Phyllophorus liuwutiensis (Echinodermata: Holothuroidea: Phyllophoridae) to that of other sea cucumbers. Issue 8 (17th July 2020) - Yang, Fuyuan; Zhou, Chen; Tran, Ngoc Tuan; Sun, Zaiqiao; Wu, Jianshao; Ge, Hui; Lu, Zhen; Zhong, Chenhui; Zhu, Zhihuang; Yang, Qiuhua; Lin, Qi
Abstract : Sea cucumber species are abundant (>1400 species) and widely distributed globally. mtDNA sequencing is frequently used to identify the phylogenetic and evolutionary relationships among species. However, there are no reports on the mitochondrial genome of Phyllophorus liuwutiensis . Here, we performed mtDNA sequencing of P. liuwutiensis to examine its phylogenetic relationships with other echinoderms. Its mitochondrial genome (15 969 bp) contains 37 coding genes, including 13 protein‐coding genes, 22 tRNA genes and 2 rRNA genes. Except for one protein‐coding gene ( nad6 ) and five tRNA genes encoded on the negative strand, all other genes were encoded on the positive strand. The mitochondrial bases of P. liuwutiensis were composed of 29.55% T, 22.16% C, 35.64% A and 12.64% G. The putative control region was 703 bp in length. Seven overlapping regions (1–10 bp) were found. The noncoding region between the genes ranged from 1 to 130 bp in length. One putative control region has been found in the P. liuwutiensis mitogenome. All of the tRNA genes were predicted to fold into a cloverleaf structure. In addition, we compared the gene arrangements of six echinoderms, revealing that the gene order of P. liuwutiensis was a new arrangement. Abstract : In this paper, we analyzed the mitochondrial genome of Phyllophorus liuwutiensis . We examined genome composition, base composition, codon usage of protein‐coding genes and gene arrangement. In addition, we compared the gene arrangements of six echinoderms, revealing that the gene order of P. liuwutiensis was a new arrangement.